2001
DOI: 10.1034/j.1600-0609.2001.066004245.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased amount of mpl and reduced expression of glycoprotein IIb/IIIa and glycoprotein Ib on platelets from patients with refractory anemia: analysis by a non‐isotopic quantitative ligand binding assay and immunofluorescence

Abstract: Using a non-isotopic ligand binding assay and immunofluorescence, we examined the amount of mpl, glycoprotein IIb/IIIa (gpIIb/IIIa) and glycoprotein Ib (gpIb) on platelets from healthy volunteers and patients with refractory anemia (RA). For the analysis of mpl expression, we applied both a non-isotopic ligand binding assay and immunofluorescence using anti-mpl monoclonal antibody, and compared the results from both methods. The non-isotopic ligand binding assay has been developed in our laboratory and is suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…34 Given the large number of myeloid and nonmyeloid antigens we have evaluated, our work goes beyond a number of the previously published FC studies of myelopoiesis that have evaluated relatively few antigens. [5][6][7][8][9][10][11][12][13][14]28 Our study also differs from the more extensive previous studies that, like ours, have evaluated a broad range of myeloid and nonmyeloid antigens, [24][25][26]29 in that those studies all used 3-color FC. The 4-color approach permits the evaluation of more complex relationships among antigens during the course of myeloid maturation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…34 Given the large number of myeloid and nonmyeloid antigens we have evaluated, our work goes beyond a number of the previously published FC studies of myelopoiesis that have evaluated relatively few antigens. [5][6][7][8][9][10][11][12][13][14]28 Our study also differs from the more extensive previous studies that, like ours, have evaluated a broad range of myeloid and nonmyeloid antigens, [24][25][26]29 in that those studies all used 3-color FC. The 4-color approach permits the evaluation of more complex relationships among antigens during the course of myeloid maturation.…”
Section: Discussionmentioning
confidence: 95%
“…(2) decreased expression of c-mpl, glycoprotein IIb/IIIa, and glycoprotein Ib on platelets from patients with refractory anemia (RA) 7 ; (3) dyssynchronous expression of CD11b and CD16 in the developing neutrophils of patients with MDS 8 ; (4) aberrant coexpression of CD14 and CD66 on the myeloid cells in a subset of MDSs 9 ; (5) decreased CD10 on neutrophils in MDSs 10 ; (6) changes in a variety of leukocyte activation antigens, including FcR I, FcR II, and FcR III, in MDSs 11 ; (7) greater variability in the expression of CD38, CD71, CD13, and CD33 in RA vs normal marrow or marrow involved by aplastic anemia 12 ; and (7) aberrant coexpression of CD56 on myeloid blasts in MDSs. 13,14 Two recent studies identified immunophenotypic abnormalities among relatively mature myeloid cells in the bone marrow 15 and peripheral blood neutrophils 16 of patients with MDSs, including decreased side light scatter, 15,16 decreased CD10, 15 and increased HLA-DR, 15 CD11a, 16 and CD66.…”
Section: Cytogenetically Abnormal Cases Demonstrating the Strong Conmentioning
confidence: 99%
“…Izumi and colleagues 51 found that there was decreased surface expression of GPIb and GPIIb/IIIa in the refractory anemia subtype of MDS. They also found that the thrombopoietin receptor, mpl (assessed by the binding of a murine monoclonal antibody against mpl), was significantly decreased on MDS platelets evaluated by flow cytometric analysis.…”
Section: Myelodysplastic Syndromesmentioning
confidence: 99%